A New Geological Map of Formation Distribution on Southern Part of South China Sea:; Natuna Island, Indonesia. (May 2019) - Kausarian, H; Lei, S; Lai, G T; Cui, Y; Suryadi, A
Abstract: Natuna Island is located at the outer part of the Indonesian territory and also as the end part of South China Sea at the south. Natuna consists of the islands that are surrounded by coral reefs and composed by sedimentary rock and sediment surface (alluvium). Natuna is a part of the Sunda group (Sundaland) which evolved through tectonic events (on the east) and volcanic activity, the formation of this island occurred in late Triassic time. Survey (field observation) applied for geological mapping by sample analyzing and tracking using handheld GPS. This research uses Natuna geological map from geological research and development center of Indonesia in 1994 with the scale of 1: 250, 000 and interpretation of satellite imagery from the year 2015 with scale 1: 50, 000 as reference material. The new spreading of formation distribution is seen in the Raharjapura Formation which has the lithology of alternating sandstone and repeating limestone spread across the north to the southwest and dominates the arrangement of formations in this island. Another new spreading occurs in the Eastern for Pengadah Formation, this formation has conglomerate lithology, sandstone aligned with Raharjapura's formation. Hydrocarbon outcrop also found in the northeastern region of Natuna, this is a common thing because the Natuna islands are famous for its natural wealth of oil and gas. The final result is an updated geological map showing significant changes to the distribution of rock formations and alluvium and also propose the idea for developing this island as the vital area for Indonesian territory border.